Strategies for Character Building for Students Majoring in Office Administration at SMK Nasional Makassar - Khairunnisa M; Sitti Hardiyanti Arhas; Nasir Nasir; Muallim Muallim (ASHA Publishing, 2025)
This study aims to find out the character formation strategy of students of the Department of Office Administration of the Makassar National Vocational School. Character formation in the Vocational High School (SMK) environment is very important, especially in preparing students to not only have technical skills but also strong moral and social values. Characters such as discipline, responsibility, and cooperation are the main foundations in dealing with the world of work and community life in general. In the world of vocational education, character formation often receives less attention than the mastery of technical skills, even though the two should be balanced. This study uses a qualitative descriptive approach. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The informants consist of educators, students, and school management. The data was analyzed using the interactive model of Miles, Huberman, and Saldana and combined with SWOT analysis to formulate a character-strengthening strategy. The results showed that most students demonstrated good responsibility, discipline, and cooperation, although there were still several challenges such as low intrinsic motivation, the influence of the outside environment, and inconsistencies in the application of character values. The strategies implemented by the school include an exemplary teacher approach, project-based learning, extracurricular activities, and strengthening the role of parents and BK teachers. The recommendations from these results emphasize the importance of implementing holistic learning methods, strengthening a positive school climate, and increasing the capacity of educators in guiding students' character. Character building is not an instant process but requires continuity, for example, and synergy between schools, families, and communities. With the right strategy, vocational school students are expected to be not only technically competent but also ethically and socially superior. This study offers a distinct contribution to the existing literature by highlighting how character-building strategies in vocational schools operate through a combination of classroom learning, extracurricular activities, and teacher modeling.